THE EFFECT OF PAIKEM APPROACH ON STUDENTS’ LEARNING OUTCOMES ON THE THEME OF LINGKUNGAN SAHABAT KITA AT GRADE V SD HARAPAN BARU MEDAN ACADEMIC YEAR 2019/2020 - Florentina Br Purba; Darinda Sofia Tanjung; Rumiris Lumban Gaol (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research aimed to find out the effect of PAIKEM approach on student’s learning outcomes on the theme of “Lingkungan Sahabat Kita” at grade V SD Harapan Baru Medan academic year 2020-2021. This research utilized descriptive analytic methods. The population of this study was the entire grade V students at SD Harapan Baru Medan for as many as 68 students. The samples were chosen by simple random sampling and it was obtained class V-C which numbered 31 students as the samples. The results of this study showed that after implemementing PAIKEM Approach, the students’ learning outcomes fell into an excellent category with an average of 8.0. The results of the correlation test obtained the coefficient value of 0.723 meaning that rcount ( 0.723) ≥ rtable; thus, Ha was accepted. It was indicated that PAIKEM approach strongly influenced the students’ learning outcomes on the theme of “Lingkungan Sahabat Kita” at grade V SD Harapan Baru Medan. It could also be seen from the results of t-test in which tcount ≥ ttable which was 5,638 ≥ 1,695; thus, that Ha was accepted. This showed a significant positive influence of the use of PAIKEM approach on students' learning outcomes on the theme of “Lingkungan Sahabat Kita”at grade V SD Harapan Baru Medan academic year 2020/2021.